Effect of Active and Passive Smoking on Retinal Nerve Fibre Layer and Ganglion Cell Complex - Amany Abd El-Fattah El-Shazly; Yousra Ahmed Thabet Farweez; Lamia Salah Elewa; Yasser Abdelmageuid Elzankalony; Botheina Ahmed Thabet Farweez (Journal of Ophthalmology)
Aim. To evaluate the possible structural and functional changes in the retinal nerve fibre layer (RNFL) and the ganglion cell complex (GCC) of chronic smokers and compare them with those of passive healthy smokers using spectral domain optical coherence tomography (SD-OCT) and pattern electroretinogram (PERG). Materials and Methods. We include 80 active chronic smokers and 80 age- and sex-matched healthy passive smokers. After a full ophthalmological examination, SD-OCT and PERG were tested for all participants. Urinary levels of cotinine and creatinine with subsequent calculation of the cotinine creatinine ratio (CCR). Results. Inferior and superior quadrants of RNFL were thinner in group I, but nasal and temporal quadrants did not show significant difference between the groups. There were no significant differences of GCC values between the two groups. There was no significant difference of PERG-P50 amplitude and latency; however, PERG-N95 showed significant difference between the two groups. Multiple regression analyses demonstrated that the number of cigarettes/day, urinary cotinine, and PERG-N95 amplitude are the most important determinants for both superior and inferior RNFL thicknesses. Conclusion. RNFL thickness decreases in chronic, healthy, heavy cigarette smokers, and this thinning is related to the number of cigarettes/day, urinary cotinine, and PERG-N95 latency and amplitude.